Pervasive subduction zone devolatilization recycles CO2 into the forearc - E. M. Stewart (Nature Portfolio, 2020)
The fate of subducted CO2 remains debated, with estimates mainly from numerical predictions varying from wholesale decarbonation of the shallow subducting slab to massive deep subduction of CO2. Here, the authors present field-based data and show that ~40% to ~65% of the CO2 in subducting crust is released via metamorphic decarbonation reactions at forearc depths.